STRUKTUR KOMUNITAS PLANKTON SEBAGAI BIOINDIKATOR KUALITAS AIR DI SUNGAI UPANG DESA TANAH BAWAH KECAMATAN PUDING BESAR - Mirwan Suhadi; Andi Gustomi; Okto Supratman; Okto Supratman (Akuatik: Jurnal Sumberdaya Perairan, 2020)
This Research Is For Analyzing The Structure Of The Plankton Commmuity Also Analyzing The Quality Of The Water And Also The Relationship Or Connection Between The Plankton Against Environment At Upang River, Tanah Bawah Village, The Sub-Disctrict Of Puding Besar. Time And Place Of This Research Was Done In January 2020 At Upang River. Sampling Was Choosen By Doing A Method Called Purposive Sampling That Was Divided Into 3 Research Stations. Plankton Data Taking Was Done By Filtering The River Water 100 Litres Using A Tool Called Plankton Net. The Output Result From Anaylzing The Structure Of The Plankton Community Was 4 Classes And 10 Species Of Plankton That Was Found At The End Of Upang River, Tanah Bawah Village. And The Species Were: Acicular Sp, Navicular Sp, Bacilaria Paradoxa, Isthmia Sp, Pactylococcopsis Sp, Spirulina Laxxissima, Lingbya Agardh, Chrysophyta Sp, Spyrogyra Sp And Asterionela Formosa. The Abundance Of Plankton Itself Between 792-1325 Ind/L. Diversity Index (H’) Is Classiefied In The Diversity That Ranges From 1,41-1,83. Low Index ( D ) Is Dominated Around 0,19-0,33 And Uniformity Index ( E ) Is Also Dominated Around 0,68- 0,83. The Result Of Analysis Between Plankton With Environment Was Done By Using Pca That We Got By Analyzing The Plankton That Has High Correlation Against The Nitrat Parameter, Current And Depth Of The Water And Low Correlation Towards Light, Bod, Tss And Do. Highly Correlated Relationship Means That The Abundance Of Plankton Is Very Influential Towards The Paramater Itself, Otherwise Low Correlated Relationship Means The Abundance Of Plankton Is Less Effective Towards The Parameter. Keywords: Plankton, Water Quality, Community Structure, Upang River.